THE EFFECT OF PROFITABILITY, ASSET GROWTH AND OPERATING LEVERAGE ON CAPITAL STRUCTURE WITH COMPANY SIZE AS A MODERATING VARIABLE - Santioso, Linda; Daryatno, Andreas Bambang (International Journal of Application on Economics and Business, 2024)
Capital structure plays an important role in maintaining the survival of the Company. The better the capital structure owned by the Company, the better the Company will be in financing the Company's operations, even more able to survive in the event of an economic shock. The purpose of this research is to obtain empirical evidence of the effect of Profitability, Asset Growth, and Operating Leverage on Capital Structure with Company Size as a moderating variable. This study uses purposive sampling as its sampling technique and uses primary consumer sector companies as research samples. The data used in this study comes from the Financial Statements of companies listed on the Indonesia Stock Exchange. Data processing in this study used the Smart PLS program. The results showed that the independent variables of Profitability, Asset Growth, Operating Leverage had no significant positive effect on the Company's Capital Structure. But when the profitability variable is moderated by company size, it produces a significant influence on the capital structure, while for the Asset Growth variable moderated by company size, although it has increased, it still does not significantly affect the Company's Capital Structure. From the result above, it can be concluded that the use of profitability is the key of all independent variables in influencing the capital structure. Companies that use internal funds will be better at financing the Company's operations, increasing assets, assessing the size of the company, namely utilizing the Company's retained earnings to increase the growth and survival of the Company.